CHANGING CHARACTERISTICS OF MOTOR OILS IN GAS ENGINES OF GREAT POWER - S. V. Korneev; S. V. Pashkevich; A. O. Trishkin; R. V. Buravkin (Вестник СибАДИ, 2017)
The article presents the results of studying the characteristics of engine oil G-Profi PSN 40, designed for use in gas engines of power plants fitted to mine. It reflects the issues of the changing characteristics of the engine oil during use and determine the frequency of their replacement. Examines the changing characteristics of engine oils as kinematic viscosity, base number, acid number, and also evaluated the tribological properties of the content of wear products. The conclusions about the feasibility of using the investigated engine oil.